Isolation and screening of proteolytic bacteria from freshwater fish Cyprinus carpio - N, Balaji; M, Rajasekaran K; N, Kanipandian; V, Vignesh; R, Thirumurugan (International Multidisciplinary Research Journal, 2012)
The present study was undertaken to isolate and characterize the protease producing potent bacteria from gastro intestinal tract of the freshwater fish Cyprinus carpio. The protease producer was characterized as Bacillus sp. morphologically and biochemically. The optimization studies for growth and proteases production of the isolate Bacillus sp. was carried out. The optimum temperature for the isolated Bacillus sp. was 350C but the optimum temperature for the protease production was 450C, the optimum pH was 7.0 in which the isolate produced 18 mMol/ml and showed a remarkable number of Colony Forming Unit. Hence, it was focused to study the intestinal Bacillus sp. in freshwater fish and its protease enzyme.